2014
DOI: 10.1103/physrevapplied.2.014004
|View full text |Cite
|
Sign up to set email alerts
|

High-Visibility On-Chip Quantum Interference of Single Surface Plasmons

Abstract: Quantum photonic integrated circuits (QPICs) based on dielectric waveguides have been widely used in linear optical quantum computation. Recently, surface plasmons have been introduced to this application because they can confine and manipulate light beyond the diffraction limit. In this study, the on-chip quantum interference of two single surface plasmons was achieved using dielectric-loaded surface-plasmon-polariton waveguides. The high visibility (greater than 90%) proves the bosonic nature of single plasm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…In fact it has been experimentally demonstrated that SPPs exhibit single particle statistics [1], [34], [57], [73]. Recently, there have been some remarkable experiments that have shown quantum interference between SPPs [22], [35], [45], [49], [58] in particular by performing a plasmonic version of the Hong-Ou-Mandel effect [61]. An example of this iconic quantum optics experiment is represented in fig 5 [35].…”
Section: Quantising Light In Plasmonicsmentioning
confidence: 99%
“…In fact it has been experimentally demonstrated that SPPs exhibit single particle statistics [1], [34], [57], [73]. Recently, there have been some remarkable experiments that have shown quantum interference between SPPs [22], [35], [45], [49], [58] in particular by performing a plasmonic version of the Hong-Ou-Mandel effect [61]. An example of this iconic quantum optics experiment is represented in fig 5 [35].…”
Section: Quantising Light In Plasmonicsmentioning
confidence: 99%
“…The proposed gabled Si tip SPP excitation scheme can also be useful in enhanced nonlinear applications . Furthermore, such highly efficient SPP excitation technique can be useful for an easier and compact excitation of SPPs for experiments studying quantum properties of surface plasmon polaritons …”
Section: Applicationsmentioning
confidence: 99%
“…The work of Olislager et al [2] reviewed different quantum experiments with plasmons, such as Young's double-slit experiment [9], evidence of quantum superpositions of single plasmons [10][11][12][13][14], and the generation of plasmonic squeezed states [15], as well as two-particle experiments [16][17][18][19][20][21]. The studies mentioned above proved the quantum bosonic nature of plasmonic excitations.…”
Section: Introductionmentioning
confidence: 99%